Singular integral equation for an edge crack originates at the interface of two bonded half-planes - Husin, Nur Hazirah; Nik Long, Nik Mohd Asri; Senu, Norazak; Hamzah, Khairum (Springer, 2024)
This paper addresses an edge crack problem that originates at the interface of two bonded halfplanes. The crack undergoes constant shear stress. We formulate the singular integral equation (SIE) with the unknown dislocation distribution function and traction as the right-hand term, using the modified complex potentials and the continuity conditions of traction and displacement. The curve length coordinate method is applied to transform the SIE of different edge crack configurations into the SIE for a straight line on the real axis with the interval [0, a], thus requiring fewer collocation points. A semi-open quadrature rule is used to solve the obtained SIE. The stress intensity factors (SIFs) of Mode I and Mode II at the crack’s tip are analyzed. Some numerical examples are provided to demonstrate the behavior of SIFs for different edge crack configurations with different values of the elastic constant ratio.